Practical tips for facilitating research - Bent, Moira (Practical tips for library and information professionals, 2016)
This practical guide offers innovative tips and reliable best practice to enable new and experienced library and information professionals to evaluate their current provision and develop their service to meet the evolving needs of the research community. Interacting effectively with information is at the heart of all research, consequently information professionals have a key role to play in facilitating the development of researchers who are able to operate confidently and successfully in the information world. Grounded in current theory and informed by practitioners from around the world, this practical book offers a wide range of ideas and methods to assist library and information professionals in developing and managing their role in the research environment.